2012
DOI: 10.1371/journal.pone.0052682
|View full text |Cite
|
Sign up to set email alerts
|

CD271+ Subpopulation of Pancreatic Stellate Cells Correlates with Prognosis of Pancreatic Cancer and Is Regulated by Interaction with Cancer Cells

Abstract: Pancreatic stellate cells (PSCs) play a crucial role in the aggressive behavior of pancreatic cancer. Although heterogeneity of PSCs has been identified, the functional differences remain unclear. We characterized CD271+ PSCs in human pancreatic cancer. Immunohistochemistry for CD271 was performed for 31 normal pancreatic tissues and 105 pancreatic ductal adenocarcinomas (PDACs). We performed flow cytometry and quantitative RT-PCR, and assessed CD271 expression in PSCs isolated from pancreatic tissues and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 27 publications
3
32
0
Order By: Relevance
“…Each experiment was carried out in triplicate wells and independent experiments were repeated. Invasive cells were isolated by functional separation using the Matrigel invasion assay after 72 h in culture ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Each experiment was carried out in triplicate wells and independent experiments were repeated. Invasive cells were isolated by functional separation using the Matrigel invasion assay after 72 h in culture ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…The finding that PSC express Meflin indicates shared features between these two cell types, details of which should be investigated in the future. Moreover, a previous study has shown that CD271 (also known as nerve growth factor receptor), a marker of PSC and MSC, is expressed by stromal cells in PDAC and the number of CD271 + cells is associated with a better prognosis, further supporting a view that PSC are closely related to MSC . However, it remains unclear whether Meflin + CAF and CD271 + stromal cells are the same or represent distinct cell populations.…”
Section: Meflin: a Candidate Marker Of Cancer‐restraining Cancer‐assomentioning
confidence: 97%
“…Heterogeneity among PSCs within the same tumor has been observed, suggesting that various subsets of PSCs have different effects on cancer cell migration and proliferation [ 18 ] and on outcome in patients [ 19 ]. Although relatively few data exist on functional heterogeneity of stromal cells, the possibility of heterogeneity among PSC populations isolated from different patients has been put forward, indicating that different PCS phenotypes could interact differently with the cancer cells in the tumor microenvironment [ 5 ].…”
Section: Introductionmentioning
confidence: 99%